VAKSINASI DINI Bordetella bronchiseptica PADA ANAK BABI MENCEGAH KERUSAKAN SEL-SEL EPITEL BERBULU GETAR PADA MUKOSA SALURAN NAFAS BAGIAN ATAS - Chotiah, Siti (BERITA BIOLOGI, 2008)
The upper respiratory tract is lined with ciliated epithelium or brush border that functions as the primary filter to the respiratory tissue. Epithelial trauma caused by neonatal bordetellosis serves as the predisposing factor for other respiratory diseases in growing pig. The aim of this research was to evaluate the effectiveness life nonpathogenic Bordetella Bronchiseptica vaccine that used in sucking piglets in Indonesia, to prevent the damage of ciliated epithelium. Twenty four sucking piglets 2 to 3 day-old were divided into treatment group containing fourteen and nontreatment group containing ten. Each sucking piglet of treatment group was vaccinated with life nonpathogenic Bordetella Bronchiseptica vaccine by intra nasal with 0.5 ml/nostril dose containing more than72.0xl0 CFU/ml bacteria. Three weeks post vaccination 10 of those treatment group and 6 from nontreatment group were challenged against local isolate B. bronchiseptica BS9 (BCC2455) toxigenic with 4.2xlOCFU/ml dose. The clinical signs, reisolation of bacteria, and histopathological changes were observed. The result showed that 3 of 10, 5 of 6, 0 of 4, and 3 of 4 treatment and challenge sucking piglet group, nontreatment and challenge sucking piglet group, treatment and not challenge sucking piglet group,and nontreatment and not challenge sucking piglet group were found lost of cilia from most of the ciliated epithelial cells of nasal mucosa respectively. Three of 10, 4 of 6, 1 of 4, and 4 of 4 treatment and challenge sucking piglet group, nontreatment and challenge sucking piglet group, treatment and not challenge sucking piglet group, and nontreatment and not challenge sucking piglet group were found epithelial cells desquamation of nasal mucosa respectively. The results indicated that life nonpathogenic Bordetella Bronchiseptica vaccine could give 70 % protection against infection of B. bronchiseptica local isolate BS9 (BCC245) toxigenic infection and 75% wild type isolate present at the farm used for this research.